Licencias e impactos ambientales positivos en Colombia. Medidas para potenciar los beneficios ambientales en los territorios - Pérez-Muñoz, Carolina (2023)
Based on the review of the existing Colombian regulations, the essay analyzes environmental licenses, to identify methodologies, guidelines or directives for the control and monitoring of management measures, specifically to assess positive environmental impacts. To achieve this, methodologies for the presentation and monitoring of environmental studies were explored to identify the positions of the environmental authorities in the country. The essay proposes an articulation between environmental licenses and territorial planning, aimed at improving the living conditions of the population or, in other words, social welfare, as an alternative to incorporate positive impacts.